Job satisfaction and its related factors among emergency department physicians in China - Kang Li; Hongmei Chen; Zhen Tan; Xiaoxv Yin; Yanhong Gong; Nan Jiang; Fengjie Yang (Frontiers Media S.A., 2022)
BackgroundJob satisfaction is recognized as an important factor affecting the performance and quality of medical services of emergency department physicians. However, little is known about the status of job satisfaction among emergency department physicians in China. This study aimed to explore the current level of job satisfaction and its associated factors among emergency department physicians in China.MethodsA nationwide cross-sectional survey was conducted in China from July to August 2018. A total of 10,457 emergency department physicians completed the questionnaire. The structured online questionnaire collected information on socio-demographic characteristics, work-related factors, work-family conflict, and job satisfaction. Student's t-test or ANOVA were used to compare the job satisfaction scores in different characters. The generalized linear model was used to investigate the related factors of job satisfaction among emergency department physicians.ResultsThe respondents' job satisfaction average score was 12.2 ± 3.6, of which 42.01% were satisfied of which the job. The results showed that emergency department physicians over 41 years old, with a higher income and working in central and western regions were positively associated with job satisfaction. In contrast, bachelor degree and above, fixed posts, long years of service, a high frequency of night shift, perceived shortage of physicians, perceived medical errors, and higher work-family conflict scores were negatively correlated with job satisfaction among emergency department physicians.ConclusionJob satisfaction of emergency department physicians in China is low. It is suggested that hospital administrators could improve the job satisfaction of emergency department physicians by establishing an acceptable shift system, ensuring adequate emergency department staffing, increasing their income appropriately and alleviating work-family conflict.